The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1965
DOI: 10.1103/physrev.138.a1802
|View full text |Cite
|
Sign up to set email alerts
|

Axially Symmetric Paramagnetic Color Centers in Fluorapatite

Abstract: The x-ray coloration of synthetic calcium fluorophosphate (fluorapatite) crystals is shown to result from the presence of fluorine vacancy defects. Three of these defects have been studied by correlating their optical absorption bands with their electron-paramagnetic-resonance spectra, and by application of the electron-nuclear-double-resonance technique to measure the F 19 and P 31 hyperfine interactions. The models proposed for these three axially symmetric defects consist of an electron trapped at (a) an is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…The electron-like centers are associated with F -vacancies or substituting O 2-ions in the anion column: F E(I) is an electron trapped by one of two F -vacancies separated by a substitutional O 2-ion, F E(II) is an electron trapped by an isolated F -vacancy, F E(III) is an electron trapped by two F -vacancies adjacent to a substitutional O 2-ion, and F E(IV) an electron trapped by a F -vacancy adjacent to a substitutional O 2-ion. Piper et al (1965) also reported a diamagnetic center ( F B) with two electrons trapped by two F -vacancies adjacent to a substitutional O 2-ion. Center F H(I) involves a hole trapped by a substitutional O 2-ion associated with a neighboring F -vacancy (Segall et al 1962), whereas F H(II) consists of a hole trapped by an isolated substitutional O 2-ion.…”
Section: Background Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…The electron-like centers are associated with F -vacancies or substituting O 2-ions in the anion column: F E(I) is an electron trapped by one of two F -vacancies separated by a substitutional O 2-ion, F E(II) is an electron trapped by an isolated F -vacancy, F E(III) is an electron trapped by two F -vacancies adjacent to a substitutional O 2-ion, and F E(IV) an electron trapped by a F -vacancy adjacent to a substitutional O 2-ion. Piper et al (1965) also reported a diamagnetic center ( F B) with two electrons trapped by two F -vacancies adjacent to a substitutional O 2-ion. Center F H(I) involves a hole trapped by a substitutional O 2-ion associated with a neighboring F -vacancy (Segall et al 1962), whereas F H(II) consists of a hole trapped by an isolated substitutional O 2-ion.…”
Section: Background Informationmentioning
confidence: 99%
“…Center F H(I) involves a hole trapped by a substitutional O 2-ion associated with a neighboring F -vacancy (Segall et al 1962), whereas F H(II) consists of a hole trapped by an isolated substitutional O 2-ion. Piper et al (1965) noted that F H(III) and F H(IV) form during the thermal conversion from F H(I) to F H(II). They interpreted F H(III) and F H(IV) to represent stable intermediate confi gurations during the progressive loss of the F -vacancy from the neighboring O 2-ion.…”
Section: Background Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Clifford and Hill (1996) further suggested that the apatite formed in A-W systems is therefore more likely to be a mixture of fluor-and oxyapatite. Based on the pioneering electron spin resonance (ESP) studies on fluor/oxyapatites, it has been long known that O − can occupy F − sites (Segall et al, 1962;Piper et al, 1965). Nonetheless, at present, the availability of high-resolution solid-state characterization techniques such as 17 O MAS-NMR coupled with dynamic nuclear polarization (DNP) and high field 19 F MAS-NMR could provide fast and accurate elucidation of oxygen and fluorine environments in the A-W GC; however, such work is yet to be published.…”
Section: Biomedical Applications Of Apatite Glass-ceramics Orthopedicsmentioning
confidence: 99%